Effect of oxide support on Ni–Pd bimetallic nanocatalysts for steam gasification of n-C7 asphaltenes. (15th September 2015) - Nassar, Nashaat N.; Franco, Camilo A.; Montoya, Tatiana; Cortés, Farid B.; Hassan, Azfar
Graphical abstract: Highlights: Ni–Pd/γ-Al2 O3 and Ni–Pd/TiO2 NPs were prepared by the incipient wetness technique. Ni–Pd/TiO2 NPs showed the highest adsorption capacity and catalytic activity. Bimetallic NPs showed their synergistic effect toward asphaltene steam gasification. Adsorption isotherms were adequately described by the SLE model. Catalytic activity of the nanoparticles was confirmed by the OFW model. Abstract: In a previous study, we showed that Ni–Pd bimetallic nanocatalysts supported on fumed silica had better adsorption affinity and catalytic activity toward adsorption and post-adsorption decomposition of asphaltenes compared to the support without functionalization. In this study, the effect of oxide support types on the adsorption and subsequent steam gasification of adsorbed asphaltenes was studied over Ni–Pd bimetallic nanocatalysts supported on TiO2 or γ-Al2 O3 nanoparticles. X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM) and N2 physisorption at 77 K were used to characterize the crystal size and surface area of NiO and/or PdO-supported-on-TiO2 or γ-Al2 O3 nanoparticles, respectively. The type of support was shown to affect the adsorption affinity and catalytic activity of the particles; Ni–Pd/TiO2 nanoparticles showed higher adsorption capacity and catalytic activity than Ni–Pd/γ-Al2 O3, presumably due to different metal-support interaction and geometric and electronic effects on the surface. Bimetallic nanoparticles appeared to have better adsorption and catalytic behavior than monometallic nanoparticles regardless of the oxide support used, confirming their synergistic effect.